Grid-tie three-phase inverter with active power injection and reactive power compensation - Sampaio, Leonardo P.; de Brito, Moacyr A.G.; de A. e Melo, Guilherme [UNESP]; Canesin, Carlos A. [UNESP] (Elsevier, 2016)
This paper proposes a methodology for the active and reactive power flow control, applied to a grid-tie three-phase power inverter, considering local and/or regionalized power flow control necessity in the forthcoming distributed generation scenario. The controllers are designed by means of robust pole placement technique, which is determined using the Linear Matrix Inequalities with D-stability criteria. The linearized models used in the control design are obtained by means of feedback linearization, aiming to reduce system nonlinearities, improve the controller's performance and mitigate potential disturbances. Through multi-loop control, the power loop uses active and reactive power transfer adapted expressions to obtain the magnitude of the voltage and power transfer angle to control the power flow between the distributed generation and the utility grid. The methodology main idea is to obtain the best controllers with the lowest gains as possible placing the poles in the left-half s-plane region, resulting in fast responses with reduced oscillations. In order to demonstrate the feasibility of the proposal a 3 kVA three-phase prototype was implemented and a comparison with conventional controller is performed to demonstrate the proposed methodology performance. In addition, anti-islanding detection and protection against over/under voltage and frequency deviations are demonstrated through experimental results.
Keywords: Distributed generation; Feedback linearization; Linear matrix inequalities; Microgrid; Power flow control; Robust control